Is prenatal childbirth preparation effective in decreasing adverse maternal and neonatal response to labor? A nested case-control study - Kim, H.H.; Nava-Ocampo, A.A.; Kim, et al., S.K. (Acta Biomedica Atenei Parmensis, 2008)
Sophrology, based on a combination of Western relaxation therapy and Eastern yoga and meditation might decrease maternal stress during labor. This study aimed to evaluate whether prenatal sophrologic childbirth preparation may decrease maternal and neonatal adverse response associated with delivery. In a nested case-control study, 69 nulliparous, singleton pregnant women who underwent an educational course of sophrologic childbirth preparation were compared to 69 nulliparous, singleton, age- and gestational agematched pregnant women who did not receive any childbirth preparation. All babies were vaginally delivered. Groups were not different (P > 0.05) in the number of neonates born with meconium-stained amniotic fluid as well as in the number of babies with Apgar score 2 7 at 1 and 5 minutes after birth. Duration of labor was not different between groups. The number of women requiring oxytocin and delivering babies with low pH blood levels tended to be lower in the group undergoing sophrologic childbirth preparation, i.e. 58.0% vs 72.5% (P = 0.07) and 1.4% vs 10.9% (P = 0.06), respectively. In conclusion, we were unable to confirm that prenatal sophrologic childbirth preparation has a definitive role in decreasing adverse maternal and fetal response to pain or in shortening labor. Prospective cohort studies with a larger sample size or randomized trials may help to clarify this gap.